Ecografia transfontanelar com fluxo a cores em recém-nascidos prematuros Intracranial blood flow velocities evaluated by color doppler (duplex) in preterm infants - Marcelo Cardoso de Assis; Helio Rubens Machado (Arquivos de Neuro-Psiquiatria)
Com o objetivo de determinarmos, evolutivamente, a medida da velocidade do fluxo sangüíneo nas artérias intracranianas, em recém-nascidos prematuros (RNP) normais e com hemorragia intracerebral, avaliamos - no período de junho de 1994 a março de 1999 - 73 recém-nascidos prematuros. A idade gestacional variou de 28 a 36 semanas e o peso ao nascimento variou de 720g a 2530g. O diagnóstico da hemorragia intracerebral foi realizado utilizando-se a ecografia transfontanelar (EGT). Para avaliação seqüencial da medida da velocidade do fluxo sangüíneo nas artérias intracranianas os 73 foram submetidos a EGT, com Doppler pulsátil, no 3º, 7º, 30º e 90º dias de vida. Após obtermos os valores numéricos destas velocidades determinamos o indice de resistência (IR). Ao analisarmos os valores do IR, comparando-se os 2 grupos de RNP, concluimos que os valores do IR são sempre mais elevados nos RNP normais (RNP-N) que nos RNP com hemorragia intracerebral (RNP-HIC); que tanto no grupo de RNP normais quanto no grupo de RNP com hemorragia intracerebral os valores do IR decrescem significativamente com o acréscimo da idade dos neonatos. Analisando-se ainda, comparativamente, os valores do IR nos RNP com hemorragia intracerebral, em seus diversos graus, observamos não haver, evolutivamente, diferença estatisticamente significante. Analisando-se também , comparativamente, os valores do IR nos RNP com hemorragia intracerebral localizada no hemisfério cerebral direito ou esquerdo concluimos não haver diferença estatisticamente significante entre os valores do IR obtidos das artérias localizadas no hemisfério cerebral acometido comparados aos valores do IR obtidos do hemisfério cerebral não afetado. In order to ascertain the blood flow velocities in the intracranial arteries we evaluated 73 preterm neonates during a period ranging from June 1994 to March 1999. These preterm infants were divided in two separate groups, 18 healthy and 55 with intracranial hemorrhage. They were subjected to sequencial measurements of blood flow velocities in the intracranial arteries. The gestational age of the whole group varied from 28 to 36 weeks and birth weights between 720 and 2530 g. The diagnosis of the intracerebral hemorrhages in these preterm neonates were done using high resolution gray and color scale transfontanellar ultrasonography brain scans . The ultrasound evaluations were performed in the initial 3rd, 7th and 14th day of life. The 73 preterm infants were evaluated with sequencial measurements of blood flow velocity in the intracranial arteries using the Doppler technique through the anterior fontanelle. Doppler evaluation of the cerebral vessels were performed on days 3, 7, 30 and 90 of life. These evaluations were performed in the six intracranial arteries, meaning: right and left anterior and middle cerebral arteries and right and left internal carotid arteries. Doppler recordings were made using Duplex Color-Doppler system, pulse echo probe of 3,5; 5,0 and 7,5 MHz. Measuring the blood flow velocity in the cerebral arteries we obtained a maximum systolic velocity and end diastolic velocity with a rate in meters per second (m/s) for each cardiac cycle. After obtaining these numerical values for these velocities we obtained the resistance index (RI) or Pourcelot index. In a progressive way as the resistance index (RI) values were being obtained in each stage of this study they were also being checked in the cerebral arteries of healthy preterm infants and infants with intracranial hemorrhages. We also analyzed in a comparative method the values of the resistive index between the two groups of preterm infants observing their behaviour.The results obtained when comparing the RI values in the various arteries during the different stages of the study permitted us to conclude that the RI values of healthy pre-term infants were always larger than the RI values of pre-term infants with intracranial hemorrhage. We also conclude that the RI values in the healthy pre-term infants and in the pre-term infants with intracranial hemorrhages decreased progressively with the increasing age of neonates.